Effectiveness of DMSO concentration on recovery rate and viability of primordial germ cell of Gaok chicken - Tatan Kostaman; Tuti L. Yusuf; M. Fachrudin; M. A. Setiadi (Indonesian Center for Animal Research and Development (ICARD), 2017)
Recent technological developments to produce germ line chimeras with primordial germ cell (PGC) transfer into the recipient embryo provide an opportunity to conserve and retrieval of chicken genetic resources in complete form. The study was conducted to obtain the most effective DMSO percentage to recovery rate and viability of Gaok chicken PGC after freezing which will later be feasible to be transferred. In this study, the eggs of Gaok chicken were incubated for about 2.5 - 3 days to obtain embryos at stages 14 - 16. Blood retrieval was done through the dorsal aorta using micropipettes under microscope. The procedure of PGC isolation of Gaok chicken with centrifugation gradient was using nycodenz as a substance. Commercially available cryoprotectants (dimethyl sulfoxide = DMSO) were used for PGC freezing. Isolated and frozen PGCs of Gaok chicken were diluted with cryoprotectants containing 2.5; 5 and 10% DMSO in fetal bovine serum (FBS). The recovery rate of 2.5; 5 and 10% DMSO concentration were 36.4; 48.2 and 48 % respectively. The viability of PGC after freezing was significantly higher for 5% DMSO compared with 2.5% DMSO (P<0.05), but not different from 10% DMSO. It can be concluded that the concentration DMSO of 5 % was effectve contration in freezing Gaok chicken PGC.